Perencanaan Stockpile Pelabuhan pada Coal Handling Facility PT. Surya Global Makmur Kecamatan Taman Rajo, Kabupaten Muaro Jambi, Provinsi Jambi - Femi Audya Syifa; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2022)
PT. Surya Global Makmur is a company that produces coal needs which is currently in the construction stage for a Coal Handling Facility with a Terminal for Self Interest (TUKS) port on an area of ±11 hectares located in Muaro Jambi Regency, Jambi Province. The port will be used as a temporary stockpile, before the coal can be transported back by barge to consumers. Stockpile has a function as a storage place for coal and requires management that must be in accordance with the process that coal will go through. The purpose of this research is to design a stockpile that will be implemented as a coal storage management. The principle used in this study is the principle of stockpile management, namely the First In First Out (FIFO) system, which means that the first coal to enter must be the first coal to leave the stockpile area.Based on the results of the coal pile design in the stockpile area of PT. Surya Global Makmur has 7 piles of coal in the shape of a pyramid for 3 types of coal calories, namely low calories, medium calories and high calories. In the simulation of coal delivery within a period of 30 days there is a stockpile of coal in the stockpile area of 40,000 tons and is adjusted to the results of calculations using Surpac 6.6.2 software. namely 141,199 tons, the stockpile capacity of PT. Surya Global Makmur is adequate to accommodate the amount of coal. The number of tools needed in the Coal Handling Facility stockpile area are 3 units of the WA380-7 wheel loader, 4 units of the PC300-8 excavator and 5 units of the Mercy 3336K dumptruck